Double-blind randomized proof-of-concept trial of canakinumab in patients with COVID-19 associated cardiac injury and heightened inflammation. Issue 1 (29th July 2021) - Cremer, Paul C; Sheng, Calvin C; Sahoo, Debasis; Dugar, Siddharth; Prada, Robier Aguillon; Wang, Tom Kai Ming; Hassan, Ossama K Abou; Hernandez-Montfort, Jamie; Wolinsky, David A; Culver, Daniel A; Rajendram, Prabalini; Duggal, Abhijit; et al.
Abstract: Aims: In coronavirus disease 2019 (COVID-19), myocardial injury is associated with systemic inflammation and higher mortality. Our aim was to perform a proof of concept trial with canakinumab, a monoclonal antibody to interleukin-1β, in patients with COVID-19, myocardial injury, and heightened inflammation. Methods and results: This trial required hospitalization due to COVID-19, elevated troponin, and a C-reactive protein concentration more than 50 mg/L. The primary endpoint was time to clinical improvement at Day 14, defined as either an improvement of two points on a seven-category ordinal scale or discharge from the hospital. The secondary endpoint was mortality at Day 28. Forty-five patients were randomly assigned to canakinumab 600 mg ( n  = 15), canakinumab 300 mg ( n  = 14), or placebo ( n  = 16). There was no difference in time to clinical improvement compared to placebo [recovery rate ratio (RRR) for canakinumab 600 mg 1.15, 95% confidence interval (CI) 0.46–2.91; RRR for canakinumab 300 mg 0.61, 95% CI 0.23–1.64]. At Day 28, 3 (18.8%) of 15 patients had died in the placebo group, compared with 3 (21.4%) of 14 patients with 300 mg canakinumab, and 1 (6.7%) of 15 patients with 600 mg canakinumab. There were no treatment-related deaths, and adverse events were similar between groups. Conclusion: There was no difference in time to clinical improvement at Day 14 in patients treated with canakinumab, and no safety concerns were identified. Future studies could focus on high dose canakinumab in the treatment arm and assess efficacy outcomes at Day 28. Graphical Abstract: